Signifikasi Tanda dalam Larik Puisi “Risalah Min Taht Al-Maa” Karya Nizar Qabbani - Nazihah, Salma; Selviana, Ika (Universitas Al Azhar Indonesia, 2025)
This research aims to examine the symbolic elements (signifier and signified) in Nizar Qabbani's poem